TRANSFORMATIONAL LEADERSHIP IN HEALTH INSTITUTE DIRECTORS AND DIGITAL TEACHING STRATEGIES IN HEALTH STUDENTS - GALVEZ, NATHALIE PARRA (2024)
INTRODUCTION: HEALTH INSTITUTIONS REQUIRE PROFESSIONALS WITH BOTH TECHNICAL AND MANAGERIAL SKILLS TO LEAD AND MANAGE SUCCESSFULLY. EVEN BETTER IF THE HEALTH MANAGEMENT PROFESSIONALS HAVE PREVIOUSLY WORKED IN DIFFERENT AREAS, FROM AUXILIARY, TECHNICAL, TO REACHING LEADERSHIP AND DIRECTIVES. OBJECTIVE: DETERMINE THE RELATIONSHIP BETWEEN THE TRANSFORMATIONAL LEADERSHIP OF HEALTH INSTITUTE MANAGERS AND DIGITAL TEACHING STRATEGIES IN HEALTH TECHNICAL STUDENTS. METHODS: IT HAD A QUANTITATIVE APPROACH, TYPE OF APPLIED RESEARCH. THE RESEARCH IS CORRELATIONAL IN SCOPE, WITH A NON-EXPERIMENTAL DESIGN. BEFORE BEING APPLIED, THE INSTRUMENTS HAD HIGH VALIDITY DETERMINED BY EXPERT OPINION AND A HIGH LEVEL OF RELIABILITY OF CRONBACH'S ALPHA. THE SAMPLING WAS NON-PROBABILISTIC OF 48 TECHNICAL STUDENTS WHO EVALUATED THE MANAGERS OF TWO PERUVIAN TRAINING CENTERS, DURING THE LAST TWO MONTHS OF 2023; BECAUSE THE INTENTION OF STARTING WITH TECHNICAL TRAINING IS TO GO THROUGH ALL JOB LEVELS UNTIL BECOMING HEADS AND DIRECTORS OF HEALTH CENTERS AND INSTITUTIONS. RESULTS: THE HIGHEST CORRELATIONS WERE BETWEEN THE CONTENT CREATION DIMENSION OF THE VARIABLE DIGITAL TEACHING STRATEGIES IN HEALTH TECHNICAL STUDENTS, WITH THE DIMENSIONS OF TRANSFORMATIONAL LEADERSHIP, THE HIGHEST VALUE WAS 0.83 WITH THE CHARISMA DIMENSION. IT WAS CONCLUDED THAT THERE WERE SIGNIFICANT AND HIGH CORRELATION RELATIONSHIPS DETERMINED BY SPEARMAN'S RHO BETWEEN TRANSFORMATIONAL LEADERSHIP OF THE DIRECTORS OF THE HEALTH INSTITUTE FOR WORK PERFORMANCE WITH DIGITAL TEACHING STRATEGIES IN HEALTH TECHNICAL STUDENTS, DURING THE PERIOD 2023-II. © 2024, EDITORIAL CIENCIAS MEDICAS. ALL RIGHTS RESERVED.